1994
DOI: 10.1111/j.1476-5381.1994.tb14771.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional studies on α1‐adrenoceptor subtypes mediating inotropic effects in rat right ventricle

Abstract: 1 We have studied the a1-adrenoceptor subtypes mediating inotropic effects of adrenaline in rat right ventricle and the Ca2+ sources used to elicit these effects. (ZlA-Adrenoceptor-mediated contractile effects in rat vas deferens were studied for comparison in some cases. 2 Treatment with chloroethylclonidine did not affect the maximal P-adrenoceptor-mediated inotropic effects in rat right ventricle or the maximal mlA-adrenoceptor-mediated contractile effects in rat vas deferens; it did not alter the potency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Cross talk of ␣ 1A -and ␣ 1B -ARs has been reported previously in rat myocardium (Michel et al, 1994b;Deng et al,1998). Results with double ␣ 1a -and ␣ 1b -AR knockout mice have indicated that both ␣ 1a -and ␣ 1b -ARs may be required for cardiac hypertrophy (O'Connell et al, 2003).…”
Section: Discussionsupporting
confidence: 57%
“…Cross talk of ␣ 1A -and ␣ 1B -ARs has been reported previously in rat myocardium (Michel et al, 1994b;Deng et al,1998). Results with double ␣ 1a -and ␣ 1b -AR knockout mice have indicated that both ␣ 1a -and ␣ 1b -ARs may be required for cardiac hypertrophy (O'Connell et al, 2003).…”
Section: Discussionsupporting
confidence: 57%
“…However, conflicting results have been reported with regard to the allocation of distinct physiological effects to the respective receptor subtypes. In rat ventricular myocardium (Michel, Hanft & Gross, 1994) and in rabbit ventricular myocardium (Takanashi, Norota & Endoh, 1991) the positive inotropic effect of adrenaline was found to be mediated mainly by alB-adrenoceptors. In another study on rat myocardium the positive inotropic effect of phenylephrine was antagonized by blocking the alA-adrenoceptors with WB 4101 (2-([2,6-dimethoxyphenoxyethyl]aminomethyl)-1,4-benzodioxane), but not affected by the alB antagonist, chlorethylclonidine (Nagashima, 1994).…”
Section: Discussionmentioning
confidence: 90%
“…BMY 7378 inhibited [3H]-prazosin binding to right ventricular membranes (Table 1), antagonized the inotropic effects of phenylephrine (Table 2) and inhibited the phenylephrineinduced increase in PI turnover (Figure 4) (Michel et al, 1989;Yazawa & Honda, 1993) as well as to liver membranes, which contain xlB-adrenoceptors (Han et al, 1987;Faure et al, 1994). It should nevertheless be emphasized that although OlD-adrenoceptor mRNA is expressed in rat myocardium (Perez et al, 1994;Price et al, 1994;Rokosh et al, 1994;Stewart et al, 1994), it represents less than 5% of the total al-adrenoceptor mRNA (Scofield et al, 1995) and the inotropic effects of the al agonists are mainly produced TI via a1A-and alB-adrenoceptors (Michel et al, 1994b;Deng et 7 8 al., 1996). Taking into account these data, findings of the present study suggest a minor role for myocardial LXIDadrenoceptors in the inotropic responses to al agonists.…”
Section: Discussionmentioning
confidence: 99%